AUDIT SISTEM INFORMASI KEAMANAN TEKNOLOGI JARINGAN BLOKCHAIN - YUNDA, EKA DEFRI YUNDA; AKBAR, M.IKMAL (TEKNOFILE : Jurnal Sistem Informasi, 2025)
Blockchain technology has great potential with a wide range of applications and provides broad opportunities for various infrastructures. Blockchain is a decentralized technology, that having broad power to solve business problems. Blockchain is emerging as a technology that promises to ensure higher levels of data encryption and security. This research aims to analyze security in blockchain technology. Transaction protection can use blockchain Security blocks against internal, malicious, peripheral and accidental threats. Analysis was carried out on the blockchain security framework architecture and as the system security model used in blockchain technology It is necessary to integrate existing security architectures with blockchain-based applications regarding technological and organizational issues. Terminal devices, networks, and super-node servers as part of the infrastructure tier. Security contributions can be mapped according to these three levels. Research discussions also on blockchain technology security architecture, frameworks, and standards and frameworks to reduce cybersecurity risks when using blockchain technology. With this research we hope to improve the current literature on blockchain security and propose future research.